2015
DOI: 10.1097/sap.0b013e3181f8cb32
|View full text |Cite
|
Sign up to set email alerts
|

Current Evidence for Postoperative Monitoring of Microvascular Free Flaps

Abstract: Future studies need to evaluate the most promising monitoring techniques further with a focus on assessing clinically relevant outcomes, such as the flap salvage rate and the false-positive rate, and not simple clinical series reporting patient and physician satisfaction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
135
0
13

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 120 publications
(149 citation statements)
references
References 193 publications
(207 reference statements)
1
135
0
13
Order By: Relevance
“…116 Many centers use other monitoring technology in addition to these basic approaches, with some reporting improvements in flap salvage rates relative to other published series. 117 However,therearenorandomizedcontrolledtrialsinthisareaandmost publications present retrospective or prospective case series. 118 …”
Section: Postoperative Flap Monitoringmentioning
confidence: 99%
“…116 Many centers use other monitoring technology in addition to these basic approaches, with some reporting improvements in flap salvage rates relative to other published series. 117 However,therearenorandomizedcontrolledtrialsinthisareaandmost publications present retrospective or prospective case series. 118 …”
Section: Postoperative Flap Monitoringmentioning
confidence: 99%
“…Although handheld Doppler is the most commonly used adjunct to clinical examination, there are no studies evaluating it as a stand-alone technique [2]. There are two main disadvantages to its use, one being that a Doppler signal may not always be readily identifiable in all flaps, and when it is, it may be difficult to distinguish from the underlying vessels.…”
Section: Literature Reviewmentioning
confidence: 99%
“…A series of conventional monitorings for 252 head and neck free flaps reported a 98% success rate, with a 0.4% false-positive rate, and a 61.5% salvage rate [2]. The monitoring technique described was performed by the nursing staff, half-hourly on the first postoperative day, hourly on the second day, 2-hourly on the third day, and 4-hourly thereafter [2]. The success rates in other large published series were 95% and higher, although the monitoring frequency and personnel was not specified in many of these [3].…”
Section: Literature Reviewmentioning
confidence: 99%
“…In a recent systematic review, it was noted that only five monitoring techniques showed evidence of increased rates of microsurgical flap rescue compared to other clinical methods (implantable Doppler, NIRS, Laser Doppler Flowmetry, quantitative fluorescence and evaluation through photographs sent by smartphones); however, none of these methods has become widely used in clinical practice [23].…”
Section: Discussionmentioning
confidence: 99%